PENGAWASAN ZONA EKONOMI EKSKULSIF INDONESIA DI BIDANG KEAMANAN MARITIM: Studi Kasus Blue Economy Periode 2015-2019 - Robika Rohman Arifianto (2023)
As a country that is surrounded by numerous earth natural activities and lively human activities, Indonesia is one of the meeting points between the abundance of resources and the need for goods and services. This strategic position makes Indonesia potentially develop and manage its entire territory. With the ratification of the 1982 United Nations Convention on Law of the Sea (UNCLOS) by the Government of Indonesia on December 31 of 1985, through Law Number 17 of 1985, Indonesia obtained international legal protection to regulate, administrate and manage all of its marine waters under state jurisdiction with due regard to freedom of navigation based on applicable international law. However, the increasing needs of humans and the dynamics of increasingly sophisticated technology make Indonesia's territory, especially its sea waters, vulnerable to threats and harms, occurring on a local, regional, and international scale. This research was created to describe the government's steps in Indonesia Exclusive Economic Zone (EEZ) surveillance as an effort to actualize a blue economy on the 2015-2019 period. To interpret the results of the collected primary and secondary data, the researcher used a descriptive approach with a qualitative-descriptive research type. Based on the interpretation of assorted sources, it can be concluded that Indonesia still has to improve its maritime security on technical and non-technical factors through coordination with various agencies and communities and cooperation with other countries to increase the world community's trust in Indonesia as sea overseer.